The Effect of Soy Protein Concentrate Addition on the Physical, Chemical, and Sensory Properties of Strawberry Flavored Ice Cream - Dervişoĝlu, M.; Yazici, F.; Aydemir, O. (Springer, 2005)
The effect of soy protein concentrate (0, 1.5, 3, and 4.5%) on the physical, chemical, and sensory properties of strawberry flavored (0, 0.01 and 0.02%) ice cream samples was examined. All samples were analyzed for pH, titratable acidity, total solids, nitrogen, fat, ash, overrun, viscosity, meltdown, Hunter L-, a-, b- values, flavor, body and texture, and appearance. Substituting soy protein concentrate (SPC) in ice cream formula for non-fat dry milk (NFDM) positively influenced the nitrogen content, viscosity values, and melting and appearance properties of the ice cream samples while overrun values and flavor scores were negatively affected. SPC could be incorporated into the ice cream formula in the range of 1.5-3% devoid of significantly diminishing the physical, chemical, and sensory properties. © Springer-Verlag 2005.
Keywords: Ice Cream; Soy Protein Concentrate; Strawberry Flavor